The ion transport, GPCR, and RTK toolkit expression in the human cerebrovascular endothelial cell line, hCMEC/D3: an Omics perspective - Scarpellino, Giorgia; Brunetti, Valentina; Scolari, Francesca; Visentin, Luca; Biella, Gerardo Rosario; Ruffinatti, Federico Alessandro; Moccia, Francesco (Frontiers in Physiology, 2025)
The blood-brain barrier (BBB) plays a central role in maintaining the ionic milieu required for neuronal activity and in translating neuronal activity in a local elevation in cerebral blood flow (CBF). However, the molecular repertoire of the human BBB remains poorly defined. Here, we performed a systematic transcriptomic analysis of 672 genes using eight independent RNA-Seq datasets generated from the human brain endothelial cell line hCMEC/D3, the most widely used in vitro model of the human BBB. We focused on ion channels, ion transporters, G protein–coupled receptors (GPCRs), and Receptor Tyrosine Kinases (RTKs), which govern ionic homeostasis, barrier integrity, and CBF. Among the most abundantly expressed ion transporters were subunits of the mitochondrial F-type ATPase complex (F-type ATPase α subunit, F-type ATPase β subunit, F-type ATPase C subunit), reflecting the high metabolic demands of the BBB. Key regulators of intracellular Ca2+ homeostasis, including SERCA2, PMCA1/4, and SPCA1, were consistently detected, supporting efficient Ca2+ clearance across endoplasmic reticulum (ER), plasma membrane, and Golgi compartments. Our analysis of ion channels revealed a selective repertoire with prominent expression of Cl−-permeable channels (CLIC1/4, CLNS1A, VDAC1-3, VRAC) and various K+-permeable channels, including IKCa/KCa3.1, KIR2.1, KNa1.2, BKCa, KV4.1, and TREK-1. Na+-permeable channels (ENaC and NALCN), non-selective cation channels (TRP, HCN2/3), and ER- (InsP3Rs, TRICs, and putative leak channels), and lysosomes-associated (TRPML1 and TPCs) channels were also detected. Additionally, we identified transcripts for mechanosensitive channels (PIEZO1, TACAN, TMC7, TMEM63B) and gap junction proteins (Cx43, Cx45, Cx47), as well as a broad array of ionotropic and metabotropic receptors, including purinergic, adenosine, histamine, GABA, adrenergic and nicotinic receptors. Growth factor-related RTKs (FGFR, IGFR, EGFR, PDGFR, VEGFR) were consistently expressed, underscoring their role in angiogenesis, endothelial-pericyte interactions, and BBB integrity. This meta-analysis highlights the conserved expression of transporter genes across datasets, contrasted with lower and more variable expression of ion channels and receptors, suggesting that the latter may be context-dependent and dynamically regulated. These findings provide a reference framework for understanding the human BBB transportome, offering new insights into the molecular toolkit of the human BBB to support future investigations into the role of endothelial ion transport in neurological disorders.